Pembangunan Hukum Pada Aspek Budaya Hukum Masyarakat - Lia Trizza Firgita Adhilia; Wiwin, Wiwin; Aris, Ardiyanti; Jufri, Supriadi; Syahril, Muh. Akbar Fhad; Yasmin, Muhammad (Innovative: Journal Of Social Science Research, 2025)
Legal development is a crucial aspect of fostering a just and orderly society, particularly in Indonesia's culturally diverse context. This article examines the interaction between law and culture in legal development within multicultural communities. By integrating formal law with customary law, it highlights the role of law as a social change agent harmonized with local cultural values. Through community-based legal education and public participation, law can become a sustainable tool for social transformation. Challenges such as cultural resistance, legal pluralism, and limited legal awareness are discussed alongside strategies to address them. The conclusion emphasizes the significance of a synergistic relationship between law and culture to establish an inclusive, responsive, and sustainable legal system.